2016
DOI: 10.4012/dmj.2016-059
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bonding performance using Weibull statistics and evaluation of acid-base resistant zone formation of recently introduced adhesives

Abstract: Dentin bonding durability of recently introduced dental adhesives: Clearfil SE Bond 2 (SE2), Optibond XTR (XTR), and Scotchbond Universal (SBU) was investigated using Weibull analysis as well as analysis of the micromorphological features of the acid-base resistant zone (ABRZ) created for the adhesives. The bonding procedures of SBU were divided into three subgroups: self-etch (SBS), phosphoric acid (PA) etching on moist (SBM) or dry dentin (SBD). All groups were thermocycled for 0, 5,000 and 10,000 cycles fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 35 publications
(47 reference statements)
2
29
0
Order By: Relevance
“…also more than use in “total-etch” mode, may reflect a certain superiority of this adhesive interface, e.g. resulting increased stability of the self-etch bond compared to the total-etch bond as have been reported in previous studies [25,26]. Evidently, an adhesive treatment must not only be able to provide effective, immediate bonding, but this effective bonding must also be durable.…”
Section: Discussionmentioning
confidence: 84%
“…also more than use in “total-etch” mode, may reflect a certain superiority of this adhesive interface, e.g. resulting increased stability of the self-etch bond compared to the total-etch bond as have been reported in previous studies [25,26]. Evidently, an adhesive treatment must not only be able to provide effective, immediate bonding, but this effective bonding must also be durable.…”
Section: Discussionmentioning
confidence: 84%
“…10-MDP plays several important roles to dissolve the smear layer, promote monomer penetration and chemically bond to hydroxyapatite 18) . SE2 contributes to the high quality of the hybrid layer and acid-base resistant zone at resindentin interface 19) .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that saliva proteins could be employed to control mineral recovery of the lesion body 25) . Clearfil SE Bond is a two-step self-etch adhesive system containing MDP, which is as a functional monomer and has several important roles such as etching of tooth substrates, enhancing monomer penetration, and imparting the adhesives with potential for chemical interactions 22,[31][32][33][34] . It was reported that the chemical bonding potential of hydroxyapatite to Ca varied with the types of functional monomers used [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%